Prevalence of diabetes and impact on cardiovascular events and mortality in patients with chronic coronary syndromes, across multiple geographical regions and ethnicities. (6th April 2021) - Mak, Koon-Hou; Vidal-Petiot, Emmanuelle; Young, Robin; Sorbets, Emmanuel; Greenlaw, Nicola; Ford, Ian; Tendera, Michal; Ferrari, Roberto; Tardif, Jean-Claude; Udell, Jacob A; Escobedo, Jorge; Fox, Kim M; et al.
Abstract: Background: In contrast with the setting of acute myocardial infarction, there are limited data regarding the impact of diabetes mellitus on clinical outcomes in contemporary cohorts of patients with chronic coronary syndromes. We aimed to investigate the prevalence and prognostic impact of diabetes according to geographical regions and ethnicity. Methods and results: CLARIFY is an observational registry of patients with chronic coronary syndromes, enrolled across 45 countries in Europe, Asia, America, Middle East, Australia, and Africa in 2009–2010, and followed up yearly for 5 years. Chronic coronary syndromes were defined by ≥1 of the following criteria: prior myocardial infarction, evidence of coronary stenosis >50%, proven symptomatic myocardial ischaemia, or prior revascularization procedure. Among 32 694 patients, 9502 (29%) had diabetes, with a regional prevalence ranging from below 20% in Northern Europe to ∼60% in the Gulf countries. In a multivariable-adjusted Cox proportional hazards model, diabetes was associated with increased risks for the primary outcome (cardiovascular death, myocardial infarction, or stroke) with an adjusted hazard ratio of 1.28 (95% confidence interval 1.18, 1.39) and for all secondary outcomes (all-cause and cardiovascular mortality, myocardial infarction, stroke, heart failure, and coronary revascularization). Differences on outcomes according to geography and ethnicity were modest. Conclusion: In patients with chronic coronary syndromes, diabetes is independently associated with mortality and cardiovascular events, including heart failure, which is not accounted by demographics, prior medical history, left ventricular ejection fraction, or use of secondary prevention medication. This is observed across multiple geographic regions and ethnicities, despite marked disparities in the prevalence of diabetes. ClinicalTrials identifier: ISRCTN43070564